Sources of Shared Knowledge: Community Stakeholders, Undergraduate Students, and Archaeologists on an International Archaeological Dig - Sophie Baggett (The University of Alabama, 2023)
I have had the dream to become a physician and specialize in cardiology for about seven years now. As a pre-med undergraduate student at Carleton College, I knew that meant I would have to take the Medical College Admissions Test and organic chemistry, as well as get meaningful clinical experience. However, I had no idea I would also lead community outreach for a project doing archaeological field research in Peru! Although this was not a typical pre-med experience, my time with Dr. Sarah Kennedy's Proyecto Arqueológico Medio Ambiental (PAMA) in Puno, Peru, was one of the most beneficial experiences I have had during my career.